The Performance of the Baris Goak Dance in the Pujawali Ceremony at Pura Puseh, Selulung indigenous village, Kintamani, Bangli Regency - Suhendra, Eka Ari (Bali Tourism Journal, 2024)
This study explores the significance of religious ceremonies in Hindu communities, with a focus on the Pura Puseh temple and the Baris Goak dance in Selulung, Kintamani, Bali. Pura Puseh, an ancient temple of the Kahyangan Tiga, serves as a key site for rituals connected to prosperity and blessings. The Baris Goak dance, unique to Selulung, is a sacred performance that symbolically represents the battle between crows (seen as harbingers of death) and a spiritual hero, Mangku Pucangan. Rooted in cultural and historical narratives, this dance integrates traditional music, costumes, and rituals, reflecting the deep relationship between art, religion, and community identity in Balinese society. The historical development of Selulung village, driven by unity and leadership, further illustrates how these cultural practices have been preserved and continue to play a central role in maintaining spiritual and social harmony. The preservation of the Baris Goak dance, supported by village customs and regulations, highlights the enduring transmission of spiritual and cultural values across generations, ensuring the continuation of a rich heritage in the modern era.